An ultrasonographic evaluation of solitary muscular and soft tissue cysticercosis - Sharma, P; Neupane, S; Shrestha, M; Dwivedi, R; Paudel, K (Kathmandu University Medical Journal, 2010)
Background: Cysticercosis in humans is infection with the larval form (cysticercus cellulosae) of the pork tapeworm T. solium. Encystment of larvae can occur in almost any tissue. The location of cysts in order of frequency is the central nervous system, subcutaneous tissue and striated muscle, vitreous humour of the eye and, rarely, other tissues. High resolution ultrasound can be used in the diagnosis of muscular and soft tissue cysticercosis. Objective: The aim of this study is to evaluate the ultrasonographic findings in cases of muscular and soft tissue cysticercosis. Materials and methods: It was a retrospective review of the cases of muscular and soft tissue cysticercosis which were diagnosed by ultrasound during June 2007 to May 2009 in the department of Radiology and Imaging, Nepalgunj Medical College Teaching Hospital. A total of six patients were evaluated. Result: There were four males and two females. Age of the patient ranged from 18 to 50 years. All of the patients presented with a swelling with pain in five of them. There was a wide variation in the location of the cysts. In all cases ultrasound revealed a cystic lesion with an echogenic eccentric pedunculated nodule attached to the wall. The mean diameter of the cyst was 6mm. Smooth wall was present in five cases whereas one of the cysts revealed irregular wall. Pericystic inflammatory changes were seen in the adjacent muscles. Conclusion: Ultrasound is a safe and non-invasive method that can be used in the diagnosis of muscular and soft tissue cysticercosis. Key words: Muscular and soft tissue cysticercosis; ultrasound. DOI: 10.3126/kumj.v8i2.3571 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 257-260